Bahasa Remaja Ragam Jurnalistik: - Sang Ayu Putu Eny Parwati (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2014)
Adolescents have opportunity to create their language’s styles that are colloquial and can be laid inwriting. The style of the adolescents’ language are included in the group of social style that marking given social ranks that could be expressed in mass media. The languages that are used by journalist are called journalistic style. Although they were expressed in written language, the adolescents’ styles of language are spoken language styles that are written. They can be observed in every word orderthat forms sentences in RRYS Radar Bali, Jawa Pos. The purpose of this research is finding the pattern usage of Indonesian by adolencent in journalistic style by doing the observation and applying descriptive qualitative method. There are some finding of inconsistency to the application of rules in Indonesian language (1) the word spelling, (2) punctuation, (3) and diction. in the case of diction, the adolescents ’journalistic style it is due to the journalists’ lack of knowledge in the good and accurate Indonesian language and the inconsistency of journalists in expressing something in written form within formalmedia. as a consequence, the output of the study is hoped have contributions in order to guide anddevelop Indonesian language to beginner journalists.